The Transformation of 44-Day War Landscapes of Memory: From Border Village to Regional Center - Hakobyan, Gayane; Galstyan, Mihran (History and Culture, 2025)
Monuments, as significant pieces of visible material culture, serve as primary sources of “storytelling”about the prevailing values, practices, ideas, political affiliations, and identity transformations within a society during a given period. The paper examines the newly formed memory landscapes in the border settlements of the Republic of Armenia (RA) following the 44-day war, and the ways those landscapes transform moving from the border villages to the regional center. To address the main research question, we employed various data collection methods, including content and discourse analysis, expert and in-depth interviews, and unstructured observation. Using the example of Tavush region in RA, we illustrate which values and ideas prevail, and which identity narratives are preserved or reshaped when moving from the center of the region to the border settlements. Based on the study results, it can be stated that the commemoration of the war in the regional center is private and scattered, and at the official level, they remain incomplete and still in the process. However, as one moves towards the border settlements (such as Sarigyugh and Sevkar), the commemoration practices become more communal and symbolic, also taking on a heroic manifestation. In the border settlements of Tavush region (Kirants and Acharkut), the memory landscape of the 44-day war becomes an important symbol of weapons, armed heroes, and fighting border guards.